New Challenges and Opportunities of Indonesian Crude Palm Oil in International Trade - Andi Amran Sulaiman; Achmad Amiruddin; Abd Haris Bahrun; Kanazawa Yuna; Mathurada Keela (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Indonesia is one of the largest palm oil producers in the world. The palm oil industry must look at the market competition map, starting from competing countries and other export opportunities to absorb palm oil products to increase state revenues. This paper analyzes the new challenges and opportunities for Crude Palm Oil (CPO) in Indonesia in international trade. Analytical tools were Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Dynamic Product Export and X-model Potential Export. The results showed that Indonesian and Malaysian palm oil commodities obtained an RCA value of more than 1 and an RSCA value of close to 1. Indonesia is more competitive than Malaysia. The X-model showed that Indonesian CPO market share optimism is only in India and the rest is less potent. Malaysian CPO market share also has less potential. Therefore, Indonesia’s new challenges are export tariffs, obstructed access, insufficient downstream production and a black campaign. The opportunity for participation in the CPO export market is only in India compared to Malaysia, which has less potential. The two countries have less potential in destinations such as the Netherlands, USA, China and Kenya. Indonesia can take external policies by establishing cooperation with export destination countries, such as trade agreements, so that information about Indonesian palm oil is well received. Meanwhile, internal policies strengthen domestic downstream industry policies, such as the food, health, and renewable energy industries, to strengthen the domestic economy and improve the welfare of Indonesian palm oil farmers.